Schools in vulnerable contexts: Galapagos Islands’ principals and accountability - Murakami, Elizabeth; Hernandez, Frank (Revista Contemporânea de Educação, 2019)
Rural and remote areas present challenges in the organization of schools, especially when implementing new practices. In this study, we examine the leadership challenges faced by principals in the Galapagos Islands, under the Ministry of Education in Ecuador. The purpose of this case is to examine the work of principals leading schools in this unique context observing the expectations and demands for principals under a newly implemented accountability system. Significant in this study is the examination of leadership in highly vulnerable contexts, including the remote islands of Galapagos, and leadership values respective to the success of schools and communities.